2016
DOI: 10.1177/2325957414542574
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors for Overweight and Obesity among HIV-Infected Adults in Dar es Salaam, Tanzania

Abstract: Background Overweight and obesity are increasingly prevalent among HIV-infected populations. We describe their prevalence and associated risk factors among HIV-infected adults in Dar es Salaam, Tanzania. Methods A cross-sectional study was conducted to determine the proportion of patients who were overweight or obese at enrollment to care and treatment centres from 2004 to 2011. Multivariate relative risk regression models were fit to identify risk factors. Results A total of 53 825 patients were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
25
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 41 publications
11
25
3
Order By: Relevance
“…Overweight/obesity was more prevalent among participants on LTART compared to ART naïve study subjects and was higher than the reported prevalence of overweight/obesity in a previous study in Dar es Salaam [44]. In the Temprano trial, the prevalence of overweight/obesity among individuals with HIV infection increased from 27 to 32 percent after 24 months of initiation of ART [45].…”
Section: Plos Onementioning
confidence: 55%
“…Overweight/obesity was more prevalent among participants on LTART compared to ART naïve study subjects and was higher than the reported prevalence of overweight/obesity in a previous study in Dar es Salaam [44]. In the Temprano trial, the prevalence of overweight/obesity among individuals with HIV infection increased from 27 to 32 percent after 24 months of initiation of ART [45].…”
Section: Plos Onementioning
confidence: 55%
“…3 Several studies have described increasing proportions of overweight and obesity in people living with HIV/AIDS in SSA. 6 In a large cross-sectional study in Dare Salaam, Tanzania, it was found that 18% of HIV-positive individuals were overweight and 7% were obese. 7 Another study in south Africa found the prevalence of overweight as 26.2% and obesity as 46.4%, while in ivory coast it was found that 19.7% of them were overweight, and 7.2% were obese.…”
Section: Introductionmentioning
confidence: 99%
“…Outcomes included in this paper had been previously studied in this cohort, and data collection methods are described in detail elsewhere [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] . Briefly, patients received treatment according to Tanzanian National and World Health Organization guidelines [29] , [30] .…”
Section: Methodsmentioning
confidence: 99%